2020
DOI: 10.3389/fmicb.2020.00688
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Characterization of Fecal Staphylococcus epidermidis Isolates Suggests Plasticity to Adapt to Different Human Body Sites

Abstract: Staphylococcus epidermidis is a commensal species that has been increasingly identified as a nosocomial agent. Despite the interest, little is known about the ability of S. epidermidis isolates to adapt to different ecological niches through comparisons at genotype or phenotype levels. One niche where S. epidermidis has been reported is the human gut. Here, we present three S. epidermidis strains isolated from feces and show that they are not phylogenetically distinct from S. epidermidis isolated from other hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…Even though S. epidermidis is excluded from the gut with increasing age, its presence during a critical window of immune education may facilitate establishment a largely tolerogenic intestinal memory CD4 + T cell pool (Knoop et al, 2018), matching that seen in skin (Scharschmidt et al, 2015). We found that intestinal levels of S. epidermidis increased during colitis, consistent with its ability to adapt and bloom under certain inflammatory conditions (Garcia-Gutierrez et al, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Even though S. epidermidis is excluded from the gut with increasing age, its presence during a critical window of immune education may facilitate establishment a largely tolerogenic intestinal memory CD4 + T cell pool (Knoop et al, 2018), matching that seen in skin (Scharschmidt et al, 2015). We found that intestinal levels of S. epidermidis increased during colitis, consistent with its ability to adapt and bloom under certain inflammatory conditions (Garcia-Gutierrez et al, 2020).…”
Section: Discussionsupporting
confidence: 74%
“…Comparative genomic analysis of this strain focused more on the antibiotic resistance and its virulence gene arsenal. A very recent study reported three S. epidermidis strains isolated from fecal sample of a healthy individual ( Garcia-Gutierrez et al, 2020 ). It was shown that these strains are not phylogenetically distinct from S. epidermidis isolated from other human body sites.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the prevalence and function of S. epidermidis in the adult gut are scarce. It has been shown that strains of S. epidermidis from the gut or skin do not differ essentially in their ability to form biofilms and pathogenicity (34). A recent study has identified the gut as a reservoir and origin of bloodstream infection with S. epidermidis , thus challenging the informal dogma that this infection originates exclusively from the environment or the skin (35).…”
Section: Discussionmentioning
confidence: 99%